2016
DOI: 10.1371/journal.pone.0155791
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cigarette Smoke Condensate on Oxidative Stress, Apoptotic Cell Death, and HIV Replication in Human Monocytic Cells

Abstract: While cigarette smoking is prevalent amongst HIV-infected patients, the effects of cigarette smoke constituents in cells of myeloid lineage are poorly known. Recently, we have shown that nicotine induces oxidative stress through cytochrome P450 (CYP) 2A6-mediated pathway in U937 monocytic cells. The present study was designed to examine the effect of cigarette smoke condensate (CSC), which contains majority of tobacco constituents, on oxidative stress, cytotoxicity, expression of CYP1A1, and/or HIV-1 replicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
85
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 55 publications
7
85
0
Order By: Relevance
“…It is logical to claim that harmful effects of smoking on antioxidant system are based on daily dose. Review of other studies showed that smoking is a major risk factor for acceleraion of periodontal diseases, and this effect is dose-dependent (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…It is logical to claim that harmful effects of smoking on antioxidant system are based on daily dose. Review of other studies showed that smoking is a major risk factor for acceleraion of periodontal diseases, and this effect is dose-dependent (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…This cell line was termed U1 [208]. Like with HL-60, the U-937 cell line has been used in several types of experiments including experiments to examine what is needed to reactivate the integrated virus [209][210][211][212][213][214] and most recently in using CRISPR/cas9 technology to excise HIV out of cells as a potential "cure" strategy [215].…”
Section: U-937 and Thp-1mentioning
confidence: 99%
“…U1 cells were cultured and differentiated as described previously (13). Cells were treated with 3 μg/ml of DRV (C max of oral 400 mg QD), 1 μg/ml of RTV (C max value of oral 100 mg QD), and 20 mM ethanol (~0.08% blood alcohol content (BAC) for mild-to-moderate drinking).…”
Section: Methodsmentioning
confidence: 99%